Wars and Sanctions: Do Libraries Have a Role to Play?. Issue 3 (3rd July 2022) - Adetayo, Adebowale; Ajayi, Khadijat; Komolafe, Ranmilowo
ABSTRACT: This research sought to investigate the roles of libraries during and after wars, as well as Nigerian students' support for sanctions against nations that start wars. Data were analyzed using descriptive statistics. Of the 295 survey respondents, 73.9% supported sanctions, either strongly or partially, on nations that start wars anywhere in the world. However, 57.3% would prefer that sanctions be avoided if ordinary people will suffer as a result of the economic impact. Organizing war resolution seminars, distributing war resolution books, answering users' questions about wars, judiciously sharing current war news with library users, and providing a venue for dialogs about ongoing war are the most useful roles that libraries may play during wartime. Libraries can provide up-to-date information on government aid eligibility and accessibility, financial information resources for financial stability, community rebuilding books, and a location for postwar conversation in the aftermath of a war. The study proposes that libraries in warring nations take proactive actions by conducting war resolution seminars and providing appropriate materials related to war resolution, as well as taking proactive actions in the aftermath of wars, such as collaborating with governments to ensure that libraries are regularly provided with information about aid and recovery.